2021
DOI: 10.1038/s41598-021-84443-y
|View full text |Cite
|
Sign up to set email alerts
|

Knocking out alpha-synuclein in melanoma cells dysregulates cellular iron metabolism and suppresses tumor growth

Abstract: The protein alpha-synuclein (α-syn) is unusual because, depending on its conformation and the type of cell in which it is expressed, it is pro-death or pro-survival, triggering neurodegeneration in Parkinson’s disease and enhancing cell survival of some melanomas. To probe the function of α-syn in melanoma, we used CRISPR/Cas9 to knockout SNCA, the gene that codes for α-syn, in SK-Mel-28 melanoma cells. The SNCA-knockout clones in culture exhibited a decrease in the transferrin receptor 1 (TfR1), an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 55 publications
(38 reference statements)
4
52
0
Order By: Relevance
“…48,70,113 Turriani et al 69 reported a basal level of SNCA expression within healthy skin tissue, which was increased in vertical growth phase and metastatic growth phase melanoma tissue, the most aggressive stages of melanoma growth and progression. In addition, work from Shekoohi et al 114 has shown that knocking out SNCA in SK-MEL 28 cells suppressed tumor growth. Does this suggest that α-syn is ubiquitously expressed in melanocytes, where it normally acts to promote cell survival but when upregulated leads to uncontrolled growth, that is, melanoma?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…48,70,113 Turriani et al 69 reported a basal level of SNCA expression within healthy skin tissue, which was increased in vertical growth phase and metastatic growth phase melanoma tissue, the most aggressive stages of melanoma growth and progression. In addition, work from Shekoohi et al 114 has shown that knocking out SNCA in SK-MEL 28 cells suppressed tumor growth. Does this suggest that α-syn is ubiquitously expressed in melanocytes, where it normally acts to promote cell survival but when upregulated leads to uncontrolled growth, that is, melanoma?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Heme metabolism was the second most enriched pathway in CTCs at progression. Intriguingly, leading edge genes analysis identified key regulators of iron metabolism (SCNA, HMBS and TFRC; data not shown), which are frequently upregulated in cancer cells (Shekoohi et al, 2021). Considering that Heme metabolism pathway is found enriched exclusively in the CTC compartment and that the heme structure is an essential cofactor for enzymatic complexes of the electron transport chain and the cytochromes, we posit that this enrichment reflects augmented tumor-specific metabolic requirements at progression.…”
Section: Resultsmentioning
confidence: 98%
“…α-syn is frequently expressed in various brain tumours and melanoma [42, 43] and its upregulation has been linked to aggressive phenotypes of meningiomas [44]. Moreover, loss of α-syn results in dysregulation of iron metabolism and suppression of melanoma tumour growth [45]. Oncogenic activation of synuclein contributes to the cancer development by promoting tumor cell survival via activation of JNK/caspase apoptosis pathway and ERK and by providing resistance to certain chemotherapeutic drugs [46, 47], suggesting synuclein as a new therapeutic target for future treatment to overcome resistance to certain chemotherapeutic.…”
Section: Resultsmentioning
confidence: 99%